Limitation of Liability of Corporate Organs in the Establishment of a Sole Proprietorship Limited Liability Company - Febri Jaya; Windi Afdal (Universitas Islam Sultan Agung, 2026)
The type of research by the author in this study is normative legal research to involves and examining applicable laws and regulations as well as other relevant legal literature, commonly referred to as secondary data, in order to address specific legal issues in accordance with the research object. The liability of a limited liability company's organs is generally limited to the shares held in the company. However, in a Sole Proprietorship Limited Liability Company, management is carried out by the same person, both as Directors and as Meeting Decision-makers under the Job Creation Law. Therefore, in practice, there are many potential conflicts of interest that cause individuals who act as both founders and managers of a Limited Liability Company to be liable for their personal assets, provided that their errors and negligence can be legally proven in the Court where the Limited Liability Company is legally registered.